Implementation of a surgical site infection prevention bundle: Patient adherence and experience. Issue 1 (10th December 2021) - Hockett Sherlock, Stacey; Suh, Daniel; Perencevich, Eli; Reisinger, Heather Schacht; Streit, Judy; Frank, Amy; Clore, Gosia; Ohl, Madeline; Speicher, Dina; Herwaldt, Loreen; Schweizer, Marin L.
Narrative Abstract: We evaluated barriers and facilitators to patient adherence with a bundled intervention including chlorhexidine gluconate (CHG) bathing and decolonizing Staphylococcus aureus nasal carriers in a real-world setting. Survey data identified 85.5% adherence with home use of CHG as directed and 52.9% adherence with home use of mupirocin as directed.